1996
DOI: 10.1111/j.1365-3016.1996.tb00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine and cigarettes: a comparison of risks

Abstract: In order to provide additional data and perspective to current clinical, policy, and legal debates surrounding the prenatal use of cocaine in the USA, a retrospective cohort study was conducted to examine effects of cocaine on selected perinatal outcomes, and to compare the relative risks of adverse perinatal outcomes among users of cocaine and users of cigarettes. Using data from a large urban perinatal registry, relative risks of selected perinatal outcomes were determined for maternal cocaine users who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…1,2,8 The present study screened all women for eligibility and did not oversample or exclude women with heavy cocaine or alcohol use, as in previous reports. 1,7,[20][21][22] A limitation of this study was that the history of use of cocaine, alcohol, tobacco, and marijuana during the periconceptional period and each trimester of pregnancy was obtained at 1 month after delivery of the infant. This method of ascertainment of drug use has the drawbacks inherent in any assessment of use by recall and may result in understatement of alcohol use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,8 The present study screened all women for eligibility and did not oversample or exclude women with heavy cocaine or alcohol use, as in previous reports. 1,7,[20][21][22] A limitation of this study was that the history of use of cocaine, alcohol, tobacco, and marijuana during the periconceptional period and each trimester of pregnancy was obtained at 1 month after delivery of the infant. This method of ascertainment of drug use has the drawbacks inherent in any assessment of use by recall and may result in understatement of alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators suggested that maternal and obstetric risk factors, lack of prenatal care, undernutrition, and effects of cocaine and nicotine on uterine blood flow might be involved in the mechanism of growth restriction. 22,[24][25][26][27][28][29] Recently, an interaction between metabolic genes and cigarette smoking was demonstrated. 12 In this study, infant birth weight, length, and head circumference were lower in the presence of multidrug use.…”
Section: Discussionmentioning
confidence: 99%
“…These include spontaneous abortion, premature onset of labour and rupture of the membranes, abruptio placenta, preterm delivery and stillbirth (Ness et al 1999), (Delaney et al 1997), (Neerhof et al 1989), (Bingol et al 1987), (Miller et al 1995), (Burkett et al 1994), (Lampley et al 1996), (Kistin et al 1996), (Feldman et al 1992), (MacGregor et al 1987), (Singer et al 1994). …”
Section: Effects Of Recreational Drug Use In Pregnancymentioning
confidence: 99%
“…the rubella virus (Leek, 1972), (Warkany, 1971); chemical agents eg. methyl mercury (Harada, 1968); and a host of risk behaviours and environmental pollutants including smoking (Kistin et al 1996), recreational drugs (Lutiger et al 1991), (Bingol et al 1987), (Martinez-Frias, 1999), (Madu et al 1999), and pollutants from land fill sites (Dolk et al 1998) (Croen et al 1997). Nevertheless, despite these efforts, the cause of the majority of congenital anomalies remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nielsen et al had shown -for maternal smoking history on the Washington State birth certificate -a sensitivity of 85-89% and a specificity of 99% based on urinary co tinine measures [19]. Self-reporting could serve as a surrogate for a set of lifestyle factors that may also correlate with SGA, such as heavy alcohol drinking [43,44] and the use of marijuana [45], cocaine [46], and opiates [47]. Out of these, opiate use is a particular problem in Appalachia [48].…”
Section: Strengths and Limitationsmentioning
confidence: 99%